Independence does not come with the method – treatment of neurogenic bowel dysfunction in children with myelomeningocele. (24th August 2014) - Wide, Peter; Glad Mattsson, Gunilla; Drott, Peder; Mattsson, Sven
Abstract Aim The aim was to evaluate and compare different bowel regimes with regard to satisfaction, faecal incontinence and independence, and the relationship to quality of life among children with myelomeningocele (MMC). Methods A questionnaire, including the health‐related quality of life instrument PedsQL 4.0™, was sent to all children aged seven to 16 years (n = 172) with MMC, treated at two centres in Sweden and one in Norway. The three centres cover a third of the population in the two countries. The response rate was 62%. Results Parents of children (30%) using antegrade colonic enemas (ACE) reported higher satisfaction (p = 0.01) than the parents of those (47%) using transanal irrigation (TAI). The children reported no significant difference. Children and parents in the ACE group reported more complete evacuation of the bowels than the TAI group. No significant difference was found in faecal incontinence or independent toileting. The children (40%) who emptied their bowels independently reported a higher quality of life. Children using TAI or ACE spent around one hour on the toilet at every bowel emptying. Conclusion TAI and ACE are effective treatments, but time‐consuming and difficult to perform independently. Higher parental satisfaction is obtained with ACE. Irrespective of method the children who can use the toilet independently report a higher quality of life, which makes efforts to support independence valuable.